Simultaneous Determination of Cortisol and Cortisone from Human Serum by Liquid Chromatography-Tandem Mass Spectrometry. (6th March 2014) - Lee, Sanghoo; Lim, Hwan-Sub; Shin, Hye-Jin; Kim, Seol-A; Park, Jimyeong; Kim, Hyun-Chul; Kim, Hyogyeong; Kim, Hyung Joo; Kim, Yun-Tae; Lee, Kyoung-Ryul; Kim, Young-Jin
Abstract : A fast, sensitive, and selective liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was validated and then the levels of cortisol and cortisone from sera of healthy adults were determined by the LC-MS/MS method. One hundred μ L of serum sample was directly extracted by adding 2 mL ethyl acetate, followed by chromatographic separation on a C18 column with a mobile phase consisting of 5 mM ammonium acetate and methanol (25 : 75, v/v). The precision, accuracy, and average recovery of the method were 1.5–5.3%, 95.4–102.5%, and 96.4% for cortisol, and 1.9–6.0%, 89.2–98.8%, and 79.9% for cortisone, respectively. The method was linear from 1.0 to 500.0 ng/mL r 2 = 0.999 for cortisol and 2.5 to 100.0 ng/mL r 2 = 0.998 for cortisone. The limits of detection (LOD) and quantification (LOQ) were 0.2 and 1.0 ng/mL for cortisol, and 1.0 and 2.5 ng/mL for cortisone, respectively. The average cortisol concentration (133.9 ± 63.7  ng/mL) of samples collected between 9:00 and 11:00 a.m. was higher approximately 4.4 times than that of cortisone (30.5 ± 10.7  ng/mL) P < 0.0001 . The average cortisone/cortisol ratio was 0.225. Therefore, the LC-MS/MS method may be useful for the diagnosis of some adrenal diseases and the assessment of 11 β -hydroxysteroid dehydrogenase (11 β -HSD) activity in clinical laboratories.